Penerimaan Mobile Banking Syariah pada Ekosistem Pesantren: Pendekatan Technology Acceptance Model - Wulan Maulidatun Nisa; Mohammad Haidar Ali (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2026)
The rapid advancement of digital technology has prompted Islamic banking institutions to enhance their service delivery through innovations in mobile banking. PT BPRS Lantabur Tebuireng has responded to this trend by launching a digital platform called Lantabur Mobile, specifically designed to streamline financial transaction processes for staff members within the Tebuireng Islamic Boarding School community. Nevertheless, the adoption rate of this application remains suboptimal, as the majority of users tend to utilize only its fundamental functionalities. The present study seeks to examine the extent to which perceived ease of use and perceived usefulness influence both the intention to use and the actual usage decisions regarding Lantabur Mobile among employees at the Tebuireng Islamic Boarding School. A quantitative research design was applied, grounded in the theoretical framework of the Technology Acceptance Model (TAM). A total of 300 respondents were recruited as research participants through a purposive sampling strategy. The collected data were subsequently analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), processed with the aid of SmartPLS software. Findings revealed that perceived ease of use exerted a positive and statistically significant influence on both perceived usefulness and intention to use. Perceived usefulness, in turn, demonstrated a positive and significant impact on intention to use. Moreover, intention to use was found to significantly and positively predict usage decisions. The mediating role of intention to use was also confirmed, bridging the relationship between perceived ease of use and perceived usefulness with usage decisions. These outcomes suggest that users' perceptions of ease and utility serve as critical determinants in fostering the acceptance and adoption of Islamic mobile banking services within a pesantren-based setting.